A bacteriophage cocktail targeting Escherichia coli reduces E. coli in simulated gut conditions, while preserving a non-targeted representative commensal normal microbiota. (3rd September 2018) - Cieplak, Tomasz; Soffer, Nitzan; Sulakvelidze, Alexander; Nielsen, Dennis Sandris
ABSTRACT: Antibiotics offer an efficient means for managing diseases caused by bacterial pathogens. However, antibiotics are typically broad spectrum and they can indiscriminately kill beneficial microbes in body habitats such as the gut, deleteriously affecting the commensal gut microbiota. In addition, many bacteria have developed or are developing resistance to antibiotics, which complicates treatment and creates significant challenges in clinical medicine. Therefore, there is a real and urgent medical need to develop alternative antimicrobial approaches that will kill specific problem-causing bacteria without disturbing a normal, and often beneficial, gut microbiota. One such potential alternative approach is the use of lytic bacteriophages for managing bacterial infections, including those caused by multidrug-resistant pathogens. In the present study, we comparatively analysed the efficacy of a bacteriophage cocktail targeting Escherichia coli with that of a broad-spectrum antibiotic (ciprofloxacin) using an in vitro model of the small intestine. The parameters examined included (i) the impact on a specific, pre-chosen targeted E. coli strain, and (ii) the impact on a selected non-targeted bacterial population, which was chosen to represent a defined microbial consortium typical of a healthy small intestine. During these studies, we also examined stability of bacteriophages against various pH and bile concentrations commonly found in the intestinal tract of humans. The bacteriophage cocktail was slightly more stable in the simulated duodenum conditions compared to the simulated ileum (0.12 vs. 0.58 log decrease in phage titers, respectively). It was equally effective as ciprofloxacin in reducing E. coli in the simulated gut conditions (2–3 log reduction), but had much milder (none) impact on the commensal, non-targeted bacteria compared to the antibiotic.